Determination of pain intensity, pain-related disability, anxiety, depression, and perceived stress in Polish adults with temporomandibular disorders: A prospective cohort study - Wieckiewicz, Mieszko; Jenca, Andrej; Seweryn, Piotr; Orzeszek, Sylwia; Petrasova, Adriana; Grychowska, Natalia; Winocur-Arias, Orit; Emodi-Perlman, Alona; Kujawa, Krzysztof (Frontiers in Integrative Neuroscience, 2022)
Background There is a need to assess a relationship between the psychoemotional state of patients and the occurrence and the intensity of pain and temporomandibular disorders (TMD) in relation to a Polish population. There are no such precision data in the literature relating to the population of big Eastern European country. The study conducted by the authors refer to a large group of male and female adult patients of the Polish population in a different age profile. As a result, this study provides a picture of the situation that also takes into account population characteristics that may affect the clinical situation of patients. Objective The aim of the study was to assess the pain intensity, pain-related disability, anxiety, depression, and perceived stress among Polish adults with TMD as well as the association between psychosocial impairment and TMD. Materials and methods This prospective cohort study included 219 adult patients from the Outpatient Clinic for Temporomandibular Disorders at the Academic Dental Polyclinic in Wroclaw. The patients completed validated questionnaires, and received a TMD diagnosis based on a standardized examination (Diagnostic Criteria for Temporomandibular Disorders) performed by a qualified dentist. A statistical analysis was carried out on the collected data. Results Myalgia was the most commonly diagnosed condition among the TMD patients. Furthermore, the prevalence of perceived stress, anxiety, and depression was high in the studied sample. Females showed more depression symptoms than males, while the level of anxiety and stress was similar in both groups. The most statistically significant correlation was observed between the group of masticatory muscle disorders and the level of depression, stress, pain intensity, and pain-related disability. Conclusion Due to the high prevalence of increased levels of anxiety, depression, and perceived stress, it is essential to screen the psychosocial status of Polish TMD adult patients. Psychosocial status may have an impact on a studied patient’s response to treatment and pain intensity, and pain-related disability. Therefore, Polish TMD adult patients should be provided with management based on an interdisciplinary approach. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT05183503].